The Contemporary in the Film My Imaginary Country - Dittus-Benavente, R (FEDERACION LATINOAMERICANA SEMIOTICA, 2025)
. For the philosopher Giorgio Agamben, contemporaneity moves away from what is untimely or extraordinarily current. To be contemporary would be to have a unique relationship with one s own time, which consists of accepting it and, at the same time, distancing oneself: something like a temporal consciousness, but that shares a voluntary and rational distancing. This work analyzes the application of this notion to the documentary My imaginary country (2022), by director Patricio Guzman. The film records the consequences of the citizen revolt that occurred in the weeks after October 2019, where one and a half million people demonstrated in the streets of Santiago, Chile, with demands that questioned the neoliberal economic model and Pinochet s Constitution. Through a semiotic reading of its story and politic discourse, a film that seeks to be more than a mere record is dissected, and where the death of the author appears highly improbable.